Deformation of the plasma concentration profile due to the modulated electron beam - Anisimov, I.O.; Borisov, O.A.; Kelnyk, O.I.; Soroka, S.V. (Вопросы атомной науки и техники, 2002)
Report is devoted to the numerical simulation of the electron beam with the longitudinal modulation moving along the concentration gradient of the planarly stratified plasma with the initially linear profile (one-dimensional model). Nonlinear modification of the plasma concentration profile due to the HF electric field excited by the beam is studied. The stationary case and initial problem were calculated.